Disruption of Interactions between Hydrophobic Residues on Nonpolar Faces is a Key Determinant in Decreasing Hemolysis and Increasing Antimicrobial Activities of α‐Helical Amphipathic Peptides. Issue 10 (25th July 2013) - Son, Mieon; Lee, Yuri; Hwang, Heeyong; Hyun, Soonsil; Yu, Jaehoon
<x xml:space="preserve">Abstract</x> To design antimicrobial peptides with decrease pore‐forming activity in eukaryotic (host) membranes, an amphipathic α‐helical model peptide composed of Leu and Lys was modified to probe the balance in antimicrobial and hemolytic activities. Among analogues with broken hydrophobic interactions, L8N derivative exhibited an 8000‐fold decrease in hemolytic activity and an eightfold improvement in antimicrobial activity, affording a 64 000‐fold increase in therapeutic index against E. coli.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>